2018
DOI: 10.1038/s41467-018-03764-1
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived IL-1β/NF-κB signaling mediates parenteral nutrition-associated cholestasis

Abstract: In infants intolerant of enteral feeding because of intestinal disease, parenteral nutrition may be associated with cholestasis, which can progress to end-stage liver disease. Here we show the function of hepatic macrophages and phytosterols in parenteral nutrition-associated cholestasis (PNAC) pathogenesis using a mouse model that recapitulates the human pathophysiology and combines intestinal injury with parenteral nutrition. We combine genetic, molecular, and pharmacological approaches to identify an essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
159
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(180 citation statements)
references
References 68 publications
20
159
1
Order By: Relevance
“…Deletion of macrophages, pharmacological antagonism of IL‐1β signaling (Anakinra), or genetic deficiency of C‐C chemokine receptor type 2, caspase‐1/caspase‐11, or IL‐1 receptor, prevented cholestasis in this model, suggesting several potential novel targets for therapeutic intervention in IFALD. ( 31 ) Similar hepatic transcriptional profiles of cytokines and bile and sterol transport proteins were reported in children with IFALD, ( 25 ) validating this mouse model.…”
Section: Pathogenesis Of Ifaldsupporting
confidence: 56%
“…Deletion of macrophages, pharmacological antagonism of IL‐1β signaling (Anakinra), or genetic deficiency of C‐C chemokine receptor type 2, caspase‐1/caspase‐11, or IL‐1 receptor, prevented cholestasis in this model, suggesting several potential novel targets for therapeutic intervention in IFALD. ( 31 ) Similar hepatic transcriptional profiles of cytokines and bile and sterol transport proteins were reported in children with IFALD, ( 25 ) validating this mouse model.…”
Section: Pathogenesis Of Ifaldsupporting
confidence: 56%
“…Inflammation triggered by macrophages induced obesity related insulin resistance [62]. Consistent with these results, previous studies had indicated that LPSmediated macrophages and IL-1β production or LPS-activated Kupffer cell through TLR4 might be early events in the pathogenesis of PNALD [63,64].…”
Section: Discussionsupporting
confidence: 67%
“…We defined the active IFALD stage as the presence of histological cholestasis and/or inflammation based on the current understanding of the IFALD pathogenesis, according to which hepatic macrophage activation and increased proinflammatory cytokine production down-regulates canalicular bile transporters via their upstream nuclear receptor regulators leading to development of cholestasis (8,37,38). At diagnosis, 70% of the patients with active IFALD exhibited both cholestasis and portal inflammation, the degrees of which were positively correlated, supporting a synergistic pathophysiological connection between the two pathologies.…”
Section: Discussionmentioning
confidence: 99%